2018
DOI: 10.3171/2018.6.gks181314
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of conformity index and gradient index in patients undergoing stereotactic radiosurgery for a single metastatic tumor

Abstract: OBJECTIVEAlthough the conformity index (CI) and the gradient index (GI), which were proposed by Paddick and colleagues, are both logically considered to correlate with good posttreatment results after stereotactic radiosurgery (SRS), this hypothesis has not been confirmed clinically. The authors’ aim was to reappraise whether high CI values correlate with reduced tumor progression rates, and whether low GI values correlate with reduced complication incidences.METHODSThis was an institutional review board–appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Based on the univariate analyses, a higher CIN was associated with an improved PFS and more patients had recurrences or died when the CIN was above the median. This is contrary to the classical opinion that a CIN closer to 1.0 is indicative of an optimal plan that maximizes the local control and minimizes toxicity [ 22 , 23 ]. This may be explained by several factors inherent to the nature of CIN and the relationship with the lesion size and shape.…”
Section: Discussioncontrasting
confidence: 68%
“…Based on the univariate analyses, a higher CIN was associated with an improved PFS and more patients had recurrences or died when the CIN was above the median. This is contrary to the classical opinion that a CIN closer to 1.0 is indicative of an optimal plan that maximizes the local control and minimizes toxicity [ 22 , 23 ]. This may be explained by several factors inherent to the nature of CIN and the relationship with the lesion size and shape.…”
Section: Discussioncontrasting
confidence: 68%
“…In a study of brain metastases SRS, Aiyama et al had reported that tumor control actually was reduced as the conformity index was increased. (22) The present study found that for tumors such as craniopharyngioma the conformity index had no relationship to tumor control or to adverse radiation effect. Instead when deliberately reducing the tumor dose near the optic system while at the same time ensuring that at least 85% of the tumor received ≥12 Gy, tumor control was improved and risk was low (Fig.…”
Section: Srs Conformity and Selectivity Conceptsmentioning
confidence: 43%
“…Third, the prescription dose was 20 Gy for each GTV in Equation (3). [18][19][20][21] The dose distribution was adjusted so that D95 (%) of each GTV was covered by 100% of the prescribed dose (Fig. 1(c)).…”
Section: A | Phantom Design and Creation Of Dose Distributionsmentioning
confidence: 99%